Austenite Grain Growth Behavior of 20Mn5 Steel Used for Heavy Hydro-Generator Shaft - Liu, M.; Ma, Q.X. (Проблемы прочности, 2018)
20Mn5 steel is widely used in the manufacture of heavy hydro-generator shaft due to its good performance of strength, toughness and wears resistance. Some researches about its hot deformation and recrystallization behavior were reported. However, the austenite grain growth behavior of 20Mn5 steel when heated under high temperature was not studied. The austenite grain growth behavior determines the grain size of steel ingot before hot forging and has a great influence on the microstructure evolution during hot forging. In this study, samples from 20Mn5 hollow steel ingot are heated to different temperatures of 850, 900, 950, 1000, 1050, 1100, 1150, and 1200°C and held for different times of 1, 3, 5, 7, 9, and 11 h before being quenched with water. The experimental results show that the austenite grain size increases with increasing temperature and holding time. When heating temperature ranges from 850 to 1050°C, the growth velocity of austenite grain is small; when heating temperature ranges from 1050 to 1200°C, the growth velocity of austenite grain increases remarkably. A two-stage grain growth model is established to predict the austenite grain size after holding under high temperature. The predicted austenite grain sizes are in good agreement with the experimental ones, which indicates that the model is reliable.